Empirical Analysis of India’s FDI inflow with Gravity and Trade Model Variables - Mohd Arif; Amjid Nadeem (International Journal of Islamic and Social Sciences (ISOS), 2021)
This paper analyses the FDI inflow in India from major trade blocs which includes EU, NAFTA and ASEAN i.e. whether the FDI inflow indeed affected by the Import, Export, and core gravity model variables by applying Gravity Model on the panel data from the period of 1 996 to 201 7. The panel data is examined by the Multi-level mixed-effect model with linear regression and ML method of estimation is used for estimating the model. The study will attempt to examine FDI Inflow relationship with the import, export and gravity model variables i.e. whether FDI Inflow is significantly dependent on the trade and gravity model variables. The study found that that export has a positive relationship with the FDI inflow in India in the case of ASEAN and EU whereas with NAFTA it has a negative relation with the export. Variables like per capita Income of India and per capita income of partner trading blocs shows a positive relationship with the FDI Inflow in India.